Insight into the micellization of dodecyldimethylethylammonium bromide (DDAB) in the presence of bovine serum albumin (BSA) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Journal of Colloid and Interface Science, 2008)
in this work, we report the effect of concentration of bovine serum albumin (BSA) on the micellization of a cationic surfactant, doclecyldimethylethylammonium bromide (DDAB). Several samples covering a wide range of concentrations of protein and surfactant have been investigated. The interactions between the moieties are investigated by measuring fluorescence quenching of BSA molecules. The aggregation number of DDAB micelles is found to be small in the presence of BSA. The formation of DDAB-BSA complex is confirmed by FTIR. Absorbance spectroscopy indicates that at higher concentration, the conformational stability of BSA in DDAB is higher. The viscosity data for protein-surfactant systems confirm conformational changes in protein chains induced by the surfactant. The cmc values for DDAB increase with increasing concentration of BSA. At higher temperatures the micellization-complexation becomes enthalpy-dominated. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: Aggregation number; BSA; conductivity; conformational stability; DDAB; FFIR; fluorescence; UV-visible; viscosity